The Real World of Power Sector Regulation - Tenenbaum, Bernard (World Bank, Washington, DC, 2012)
More than twenty countries are now reforming their power sectors. For many politicians, this reform means simply restructuring and privatizing state-owned enterprises. But, what they forget or may not know is that a government cannot regulate private power companies the way it once regulated state enterprises. The author argues that if a government is serious about attracting private investors, it has no choice but to adopt a new regulatory system that keeps promises and exercises restraint-one that is independent and open to public scrutiny.